A distribution dependence study on the impacts of health rights’ accessibility on the overwork of migrant workers in China using quantile-on-quantile method - Zhang, Shengzhi; Deng, Yanlong; Zhang, Yu (Frontiers in Public Health, 2025)
IntroductionOverwork is a typical phenomenon in developing countries, especially in China, and also a significant issue that restricts the high-quality development of labor markets. Protecting the health rights’ accessibility of migrant workers in China, addressing persistent issues of overwork, and reducing generational disparities in well-being are urgent concerns. Investigating the formation mechanisms and generational variations in migrant workers’ overwork through the lens of health rights accessibility enriches theoretical explanations of overwork’s causes while offering actionable strategies for mitigation.MethodsBased on the China Migrants Dynamic Survey (CMDS), this study empirically tests the impact of health right’s accessibility on migrant workers’ overwork and its intergenerational differences using the quantile-on-quantile regression (QQR) and composition test method.ResultsHealth rights’ accessibility significantly reduces migrant workers’ overwork, with a 1-unit improvement correlating with a 4.22% decline in overwork rate and 2.36-h weekly reduction in overwork hours. The inhibitory effect is significantly stronger among new-generation migrants compared with first-generation counterparts. Threshold sensitivity exists: significant impacts emerge only when accessibility exceeds 0.4 for first-generation and 0.2 for new-generation migrants.DiscussionIn about half of the sample cities, excessive health rights’ accessibility paradoxically increases migrants’ labor supply, revealing local policy failures.